Seeded Bermudagrass Cultivar Evaluation - J. L. Moyer (Kansas Agricultural Experiment Station Research Reports, 2015)
A year after seeding, the stand of ‘F.K.#1’ appeared better than stands of 10 of the other 13 seeded entries. By fall, 2014, stands of ‘KF-13A,’ ‘KF-13B,’ and ‘SWI-800’ along with ‘F.K.#1’ were better than stands of four of the other seeded entries. Late-summer production was higher for KF-13A and ‘Midland 99,’ the sprigged check, than for five of the other entries.
Keywords: winter hardiness; stand persistence; late-summer production